Comparison between regular additional endobiliary radiofrequency ablation and photodynamic therapy in patients with advanced extrahepatic cholangiocarcinoma under systemic chemotherapy - Möhring, Christian; Khan, Oliver; Zhou, Taotao; Sadeghlar, Farsaneh; Mahn, Robert; Kaczmarek, Dominik J.; Dold, Leona; Toma, Marieta; Marinova, Milka; Glowka, Tim R.; Matthaei, Hanno; Manekeller, Steffen; et al. (Frontiers in Oncology, 2023)
Extrahepatic cholangiocarcinoma (eCCA) remains a malignancy with a dismal prognosis. The first-line standard of care includes systemic chemotherapy (SC) and biliary drainage through stenting. Endobiliary ablative techniques, such as photodynamic therapy (ePDT) and radiofrequency ablation (eRFA) have demonstrated feasibility and favourable survival data. This study aimed to compare the oncologic outcome in patients treated with SC and concomitant eRFA or ePDT.All patients with eCCA were evaluated for study inclusion. 63 patients receiving a combination of SC and at least one endobiliary treatment were retrospectively compared.Patients were stratified into three groups: SC + ePDT (n = 22), SC + eRFA (n = 28) and SC + ePDT + eRFA (n = 13). The median overall survival (OS) of the whole cohort was 14.2 months with no statistically significant difference between the three therapy groups but a trend to better survival for the group receiving ePDT as well as eRFA, during SC (ePDT + SC: 12.7 months; eRFA + SC: 13.8 months; ePDT + eRFA + SC: 20.2 months; p = 0.112). The multivariate Cox regression and subgroup analysis highlighted the beneficial effect of eRFA on OS. Overall, combined therapy was well tolerated. Only cholangitis occurred more often in the SC + eRFA group.Additional endobiliary ablative therapies in combination with SC was feasible. Both modalities, eRFA and ePDT showed similar benefit in terms of survival. Interestingly, patients receiving both regimes showed the best OS indicating a possible synergism between both ablative therapeutic techniques.